IMPLEMENTASI MEDIA TOGA BERBASIS QR CODE PADA PEMBELAJARAN TEMATIK UNTUK MENIGKATKAN LITERASI SAINS DAN DIGITAL PESERTA DIDIK KELAS III SD - Asy'ari, Muhammad Hasan; Sudarti, Sudarti; Wuryaningrum, Rusdhianti; Wicaksono, Iwan (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
This study aims to describe the implementation of QR Code-based "Tanaman Obat Keluarga" (TOGA) media in thematic learning at SD Negeri Penawungan 02, which is located in Ranuyoso sub-district, as a means of enhancing scientific literacy and digital literacy among third-grade students. This research is descriptive in nature, and the data were collected through observation and questionnaires. The findings indicate that the use of QR Code-based TOGA media successfully improved students' scientific and digital literacy. This is evidenced by the comparison of the average pre-test and post-test scores, which showed a significant increase from 63 to 80. In other words, the percentage of students achieving mastery increased from 60% to 80%. Additionally, the use of this media enhanced students' scientific and digital literacy skills by involving the use of smartphones and QR code reader applications. Students gained a better understanding of scientific concepts such as the properties, benefits, uses, and roles of medicinal plants in health and the environment, while also becoming more proficient in operating smartphones, including connecting to the internet and using QR code reader applications. Thus, the implementation of QR Code-based TOGA media at SD Negeri Penawungan 02 in Ranuyoso sub-district has successfully enhanced the scientific and digital literacy of third-grade students.